The Liverpool duodenum-and spleen-preserving near-total pancreatectomy can provide long-term pain relief in patients with end-stage chronic pancreatitis - Sheel, Andrea R. G.; Neoptolemos, John P. (Langenbeck's archives of surgery, 2019)
Purpose Total pancreatectomy may improve symptoms in patients with severe end-stage chronic pancreatitis. This might be achieved whilst preserving both the duodenum- and spleen-(DPSPTP). Mature clinical outcomes of this approach are presented. - Methods Single-centre prospective cohort study performed between September 1996 and May 2016. Demographic, clinical details, pain scores and employment status were prospectively recorded during clinic attendance. - Results Fifty-one patients (33 men, 18 women) with a median (interquartile range) age of 40.8 (35.3-49.4) years, a median weight of 69.8 (61.0-81.5) Kg and a median body mass index of 23.8 (21.5-27.8), underwent intended duodenum-and spleenpreserving near-total pancreatectomy for end-stage chronic pancreatitis. Aetiology was excess alcohol in 25, idiopathic (no mutation) in 15, idiopathic (SPINK-1/CFTR mutations) in two, hereditary (PRSS1 mutation) in seven and one each postnecrotising pancreatitis and obstructive pancreatic duct divisum in 1. The main indication for surgery was severe pain. Findings included parenchymal calcification in 79% and ductal calculi in 24%, a dilated main pancreatic duct in 57% and a dilated main bile duct in 17%, major vascular involvement in 27% and pancreato-peritoneal fistula in 2%. Postoperative complications occurred in 20 patients with two deaths. Median pain scores were 8 (7-8) preoperatively and 3 (0.25-5.75) at 5 years (p = 0.013). Opiate analgesic use was significantly reduced postoperatively (p = 0.048). Following surgery, 22 (63%) of 38 patients of working age re-entered employment compared with 12 (33%) working preoperatively (p = 0.016). - Conclusion Duodenum-and spleen-preserving near-total pancreatectomy provided long-term relief in adult patients with intractable chronic pancreatitis pain, with improved employment prospects.
Gesehen am 14.04.2020